A novel vaccine for cervical cancer: quadrivalent human papillomavirus (types 6, 11, 16 and 18) recombinant vaccine (Gardasil®) - Vandana A Govan (Dove Medical Press, 2008)
Vandana A GovanDivision of Medical Virology, Department of Clinical Laboratory Sciences and Institute of Infectious Diseases and Molecular Medicine, Faculty of Health Sciences, University of Cape Town, Observatory, Cape Town, South AfricaAbstract: Human papillomaviruses (HPVs) are one of the most common sexually transmitted infections and remains a public health problem worldwide. There is strong evidence that HPV causes cervical, vulva and vaginal cancers, genital warts and recurrent respiratory papillomatosis. The current treatments for HPV-induced infections are ineffective and recurrence is commonplace. Therefore, to reduce the burden of HPV-induced infections, several studies have investigated the efficacy of different prophylactic vaccines in clinical human trials directed against HPV types 6, 11, 16, or 18. Notably, these HPV types contribute to a significant proportion of disease worldwide. This review will focus on the published results of Merck & Co’s prophylactic quadrivalent recombinant vaccine targeting HPV types 6, 11, 16, and 18 (referred to as Gardasil®). Data from the Phase III trial demonstrated that Gardasil was 100% effi cacious in preventing precancerous lesions of the cervix, vulva, and vagina and effective against genital warts. Due to the success of these human clinical trials, the FDA approved the registration of Gardasil on the 8 June 2006. In addition, since Gardasil has been efficacious for 5 years post vaccination, the longest evaluation of an HPV vaccine, it is expected to reduce the incidence of these type specific HPV-induced diseases in the future.Keywords: Gardasil, HPV, prophylactic vaccine, cervical disease